Increasing Children's Voluntary Physical Activity Outside of School Hours Through Targeting Social Cognitive Theory Variables. (October 2016) - Annesi, James J.; Walsh, Stephanie M.; Greenwood, Brittney L.
Introduction: Volume of moderate-to-vigorous physical activity completed during the elementary school day is insufficient, and associated with health risks. Improvements in theory-based psychosocial factors might facilitate increased out-of-school physical activity.Methods: A behaviorally based after-school care protocol, Youth Fit 4 Life, was tested for its association with increased voluntary, out-of-school physical activity and improvements in its theory-based psychosocial predictors in 9- to 12-year-olds.Results: Increases over 12 weeks in out-of-school physical activity, and improvements in self-regulation for physical activity, exercise self-efficacy, and mood, were significantly greater in the Youth Fit 4 Life group (n = 88) when contrasted with a typical care control group (n = 57). Changes in the 3 psychosocial variables significantly mediated the group–physical activity change relationship ( R 2 = .31, P < .001). Change in self-regulation was a significant independent mediator, and had a reciprocal relationship with change in out-of-school physical activity. In the Youth Fit 4 Life group, occurrence of 300 min/wk of overall physical activity increased from 41% to 71%.Conclusions: Targeting theory-based psychosocial changes within a structured after-school care physical activity program was associated with increases in children's overall time being physically active. After replication, large scale application will be warranted.